Determinan Faktor Kepatuhan Wajib Pajak Kendaraan Bermotor: Suatu Studi Empiris Di Sleman Yogyakarta - Rahmawati Hanny Yustrianthe; Dwi Haryono Wiratno; Maria Purwantini (Universitas Riau Kepulauan, 2024)
This study aims to examine the effect of eliminating tax administrative sanctions, exemption from motor vehicle title transfer fees, taxpayer awareness, tax knowledge, tax socialization, and tax authorities services on motor vehicle taxpayer compliance in Sleman, Yogyakarta. The population used in this research is all motor vehicle taxpayers registered with KPPD DIY, especially in Sleman Regency. The sample selection in this study used purposive sampling and a sample of 114 respondents was obtained. The data analysis technique uses multiple linear regression analysis. The results of the research show that the partial elimination of tax administrative sanctions and the exemption from BBN-KB sanctions have no effect on motor vehicle taxpayer compliance, except for taxpayer awareness, tax knowledge, tax socialization and fiscus services. Simultaneously, the results show that the elimination of tax administrative sanctions, exemption from BBN-KB sanctions, taxpayer awareness, tax knowledge, tax socialization, and fiscus services have an effect on motor vehicle taxpayer compliance.